Factors associated with experimentation of electronic cigarettes among Parisian teenagers in 2013. Issue 1 (December 2015) - Dautzenberg, Bertrand; Berlin, Ivan; Tanguy, Marie-Laure; Rieu, Nicole; Birkui, Pierre
Abstract Background Electronic cigarettes (e-cig.) became widely used among adults. Data are insufficient about e-cig. experimentation among youth. Methods To assess prevalence of e-cig. experimentation and associated factors among the 12 to 19 years old we analyse a cross sectional school based survey in the city of Paris, France in 2013 on a randomly selected sample of 2 % of schoolchildren (n  = 3 279). Self-report questionnaire include demographic, individual and family smoking characteristics and questions about e-cig:"Have you ever used an e-cigarette?"- "Did you use e-cigarette in the last 30 days? "-"Did you try e-cigarette as a first tobacco product? " Results In 2013, 17.9 % (564) schoolchildren reported having experienced the e-cig (boys: 19.0 %, girls: 16.8 %) compared to 9.8 % in 2012. Experimentation rate increases from 5 % among the 12 to 30 % among the 16-year-old. E-cig. experimentation was significantly associated with 11 parameters including : age >15 years (OR: 0.66 (IC95 % = 0.46–0.94)); smoking 10 cigarettes or more (OR = 5.67 (IC95 % = 3.11–10.34)), best friends and siblings smoker (OR = 1.54 (IC95 % = 1.11–2.14)) and (OR = 1.88 (IC95 % = 1.41–2.52)); experimentation of shisha (OR = 2.60 (IC95 % = 1.75–3.86)), cannabis use (OR = 1.90 (IC95 % = 1.32–2.72)); having two parents who forbid smoking (OR = 2.32 (IC95 % = 1.63–3.30)). Only 5.6 % of the study population (and 32.5 % of e-cig. experimenters (183/564)) have used it in the last 30 days; 1.7 % of the study population and 10.0 % of e-cig. experimenters were non-smokers (56/564). Conclusions Rate of e-cig. experimentation among schoolchildren increased by 8.1 % in 1 year. Non-smoking youth may use e-cig. Prospective studies are urgently needed to assess the evolution of e-cig. use both among smoking and non-smoking youth.